Properties of Yogurts Enriched with Crude Polysaccharides Extracted from Pleurotus ostreatus Cultivated Mushroom - Wojciech Radzki; Katarzyna Skrzypczak; Bartosz Sołowiej; Ewa Jabłońska-Ryś; Waldemar Gustaw (Foods, 2023)
Increasingly, consumers are looking for products with specific nutritional and health-promoting properties. The answer of the producers for this demand is fortified food. The raw material that can be used to enrich food is, among others, mushrooms. Crude water soluble polysaccharides (cWSP) were isolated from fruiting bodies of Pleurotus ostreatus (oyster) mushroom. Chemical analysis showed that they consisted mainly of carbohydrates (~61%), protein (~9%) and phenolics (~0.8%). The isolated cWSP were used to obtain enriched cow milk set yogurts. cWSP were added at the concentration of 0.1%, 0.2%, 0.3%, 0.4% and 0.5%, and milk containing no cWSP was prepared as the control. All of the variants were fermented via applying two commercially available culture starters. The addition of cWSP led to a drop in pH in the case of one starter culture. Also, the decline in total soluble solids (TSS) content was higher where cWSP was used for the enrichment. Texture profile analysis (TPA) revealed that parameters of hardness and gumminess increased along with the concentration of cWSP (reaching values approximately 7–8 times higher, compared to the control). A significant increase in syneresis level (proportional to cWSP concentration and ranging from ~10% to ~50%) was also observed after the fermentation. Fortifying milk with cWSP led to a slight increase in antioxidant capacity in FRAP assay (up to ~12%) and ABTS assay (up to ~23%). The results demonstrate that using cWSP to enrich set-type yogurts is fairly limited.